'Short view' on nonprofit succession planning doesn't cut it anymore. Issue 303 (December 2014) - Unknown
Abstract : In 2005, the Bridgespan Group released the eye‐opening report "The Nonprofit Sector's Leadership Deficit, " which found the nonprofit sector would need to attract and develop some 640, 000 new senior managers over the next decade. Nearly ten years on, Ron Ries, CPA, CGMA and partner at WeiserMazars LLP, said little has been done to rectify the situation.